PARTICIPATION OF LOCAL RESTAURANTS IN SOLID WASTE MANAGEMENT IN SOUTH COAST OF GUNUNGKIDUL REGENCY, INDONESIA - Masjhoer, Jussac Maulana; Retawimbi, Aditano Yani; Sari, Yenita Sandra (Journal of Community Based Environmental Engineering and Management, 2020)
Restaurants also contribute to the generation of solid waste in tourism destinations. Participation needs to be identified because restaurants participate in utilizing and getting benefits from the tourism development. This research aims to analyze the participation of restaurants in solid waste management started from the planning stage, implementation stage, benefit stage, and evaluation stage. The research is located on the beach Ngrenehan, Ngobaran Beach, Baron Beach, Sepanjang Beach, Kukup Beach and Drini Beach. The consideration that underlies location selection is the existence of restaurants and tourists. Quantitative data were collected using a questionnaire distributed to 48 restaurant owners. The data that has been collected is then processed using simple statistics to see the frequency and average. Simplified data were then analyzed using a qualitative descriptive approach and strengthened by the results of field observations and interviews. In general it can be concluded that restaurant owners actively participate in solid waste management. Participation in the planning stage was 73%, the implementation stage was 66%, the benefit taking stage was 100%, and the evaluation stage was 81%. Restaurant owners since the early stages of participation have shown positive activity. At the implementation stage, participation is influenced by the lack of knowledge and understanding related to the solid waste they have. Perception in taking benefits is influenced by how cleanliness of restaurants is felt to be beneficial both directly and indirectly. Participation in the evaluation was shown by the majority of respondents feeling that solid waste management was in accordance with planning and expectations.